Forest gaps slow the sequestration of soil organic matter: a humification experiment with six foliar litters in an alpine forest - Ni, Xiangyin (Sci Rep, 2016)
Humification of plant litter containing carbon and other nutrients greatly contributes to the buildup of soil organic matter, but this process can be altered by forest gap-induced environmental variations during the winter and growing seasons. We conducted a field litterbag experiment in an alpine forest on the eastern Tibetan Plateau from November 2012 to October 2014. Six dominant types of foliar litter were placed on the forest floor in various forest gap positions, including gap centre, canopy gap, expanded gap and closed canopy. Over two years of incubation, all foliar litters were substantially humified especially during the first winter, although the newly accumulated humic substances were young and could be decomposed further. The forest gaps exhibited significant effects on early litter humification, but the effects were regulated by sampling seasons and litter types. Compared with the litter under the closed canopy, humification was suppressed in the gap centre after two years of field incubation. The results presented here suggest that gap formation delays the accumulation of soil organic matter, and reduces soil carbon sequestration in these alpine forests.